2015
DOI: 10.1007/s10008-015-2930-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and physicochemical properties of titanium Oxy-nitride electrocatalyst prepared by sol-gel methods for the oxygen reduction reaction purposes

Abstract: In the present article, titanium oxy-nitride (TiON), as a potential electrocatalyst for the oxygen reduction reaction (ORR), is fabricated by four different sol-gel methods. Physicochemical properties (structure, chemical composition, BET surface area, surface morphology, chemical stability, and electrochemical stability) are determined. The ORR in acid medium on these TiON electrocatalysts is evaluated and compared to the ORR on commercial Pt/C. This evaluation is based on the onset potential, charge density,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Oxynitrides can also be synthesized by nitridation of metal oxides in the flow of ammonia at elevated temperatures. , For example, tantalum oxynitride (TaO 0.92 N 1.05 ) powders were synthesized by heating the Ta 2 O 5 powders at 850 °C in ammonia and showed much higher ORR activity (onset potential = 0.8 V) than that of Ta 3 N 5 (onset potential = 0.4 V) . ZrO x N y , TiO x N y , Co x Mo 1– x O y N z , and HfO x N y nanoparticles were also synthesized and showed moderate ORR activities with onset potentials in the range of 0.7– 0.8 V. Domen et al found that the ORR onset potential of carbon supported NbO x N y nanoparticles shifted positively by 80 mV from 0.78 V for that of NbO x , indicating the role of nitrogen in the activity improvement . The same group also prepared binary (Ba–Nb–O–N) , and ternary (Ba–Nb–Zr–O–N) oxynitrides supported on carbon.…”
Section: Metal Oxides Nitrides Oxynitrides and Carbonitridesmentioning
confidence: 99%
“…Oxynitrides can also be synthesized by nitridation of metal oxides in the flow of ammonia at elevated temperatures. , For example, tantalum oxynitride (TaO 0.92 N 1.05 ) powders were synthesized by heating the Ta 2 O 5 powders at 850 °C in ammonia and showed much higher ORR activity (onset potential = 0.8 V) than that of Ta 3 N 5 (onset potential = 0.4 V) . ZrO x N y , TiO x N y , Co x Mo 1– x O y N z , and HfO x N y nanoparticles were also synthesized and showed moderate ORR activities with onset potentials in the range of 0.7– 0.8 V. Domen et al found that the ORR onset potential of carbon supported NbO x N y nanoparticles shifted positively by 80 mV from 0.78 V for that of NbO x , indicating the role of nitrogen in the activity improvement . The same group also prepared binary (Ba–Nb–O–N) , and ternary (Ba–Nb–Zr–O–N) oxynitrides supported on carbon.…”
Section: Metal Oxides Nitrides Oxynitrides and Carbonitridesmentioning
confidence: 99%
“…The most investigated metals are Fe, Co, and Ni, but some attempts to prepare partially oxidized metal (Ta, Ti, Zr, Hf, etc.) carbonitride or oxynitride samples have been carried out by the groups of Ota [32,33], Sakurai [34], and Savadogo [35,36]. However, the latter catalysts were neither investigated for their methanol tolerance properties, nor used at the cathode of a DMFC, thus they will be not discussed in the present review.…”
Section: Synthesis Of Noble Metal Free Catalystsmentioning
confidence: 99%
“…The synthesis of oxynitrides using urea as the nitrogen source primarily involves a sol-gel method. [46][47][48] In this process, titanium tetraisopropoxide and urea are mixed to obtain a precursor, which is then subjected to high-temperature calcination (800-1100 °C) under an N 2 /H 2 atmosphere, resulting in the production of oxynitride powder. However, it is worth noting that samples obtained through this method may contain rutile TiO 2 .…”
Section: Introductionmentioning
confidence: 99%